Effect of Liquid Oil on the Distribution and Reactivity of a Hydrophobic Solute in Solid Lipid Nanoparticles. (16th March 2013) - Yucel, Umut; Elias, Ryan J.; Coupland, John N.
Abstract: The performance of solid lipid nanoparticles is often modified by the addition of small amounts of liquid oil. The effects of added liquid lipid (tetradecane, C14) on the distribution and reactivity of the spin probe 4‐phenyl‐2, 2, 5, 5‐tetramethyl‐3‐imidazoline‐1‐oxyl nitroxide (PTMIO) in solid lipid nanoparticles (eicosane, C20) were investigated as a function of storage time and temperature. Emulsions prepared with blends of C14:C20 (100 % C14, 90 % C20, 99 % C20, and 100 % C20) and stabilized by sodium caseinate (1 wt%) were stored at 21.5 °C or 5 °C for 5 or 24 h prior to EPR analyses. In the liquid C14 droplets the PTMIO partitioned between the droplet and aqueous phases (70 and 30 %, respectively) independent of storage conditions. However, the proportion of probe in droplets decreased with increasing crystalline C20 concentration. The fraction of PTMIO in droplets containing C20 decreased in the following sequence: 5 h at room temperature >24 h at room temperature >24 h at refrigerated temperature and was lower in droplets with a higher proportion of C20. The residual PTMIO in semicrystalline droplets has higher polarity and lower mobility than PTMIO in liquid oil droplets suggesting it is in a layer surrounding the crystalline lipid core, and partly immobilized by interaction with the surface layer. The model of PTMIO distribution was consistent with the kinetics of PTMIO reduction by aqueous ascorbate ions.